DnaJ/Hsc70 chaperone complexes control the extracellular release of neurodegenerative‐associated proteins. (3rd June 2016) - Fontaine, Sarah N; Zheng, Dali; Sabbagh, Jonathan J; Martin, Mackenzie D; Chaput, Dale; Darling, April; Trotter, Justin H; Stothert, Andrew R; Nordhues, Bryce A; Lussier, April; Baker, Jeremy; Shelton, Lindsey; et al.
Abstract: It is now known that proteins associated with neurodegenerative disease can spread throughout the brain in a prionlike manner. However, the mechanisms regulating the trans‐synaptic spread propagation, including the neuronal release of these proteins, remain unknown. The interaction of neurodegenerative disease‐associated proteins with the molecular chaperone Hsc70 is well known, and we hypothesized that much like disaggregation, refolding, degradation, and even normal function, Hsc70 may dictate the extracellular fate of these proteins. Here, we show that several proteins, including TDP‐43, α‐synuclein, and the microtubule‐associated protein tau, can be driven out of the cell by an Hsc70 co‐chaperone, DnaJC5. In fact, DnaJC5 overexpression induced tau release in cells, neurons, and brain tissue, but only when activity of the chaperone Hsc70 was intact and when tau was able to associate with this chaperone. Moreover, release of tau from neurons was reduced in mice lacking the DnaJC5 gene and when the complement of DnaJs in the cell was altered. These results demonstrate that the dynamics of DnaJ/Hsc70 complexes are critically involved in the release of neurodegenerative disease proteins. Synopsis: The DnaJC5 protein, cysteine string protein‐α (CSPα), stimulates the release of neurodegenerative proteins through a non‐canonical exocytosis pathway. Increased expression of DnaJC5 promotes extracellular release of the microtubule‐associated protein tau, α‐synuclein, and TAR‐DNA binding protein. Release of these proteins is dependent upon both the SNARE, SNAP‐23, and the constitutively expressed Hsp70 variant, Hsc70. This function of DnaJC5 and the Hsc70 complex is unique as other DnaJs and Hsp70 variants do not promote this mechanism. This finding provides a mechanism for how aggregate‐prone proteins can exit the cell and possibly seed propagation. Abstract : DnaJC5 is a co‐chaperone for Hsc70 and SNARE‐dependent neuronal release of disease proteins such as tau, TDP‐43, or α‐synuclein.